(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
A short or medium growing season will give good results for the climatic conditions of Uzbekistan. From scientific sources we know that regardless of any type of crop, in order for the seeds to germinate on time, the soil must have enough moisture, temperature, light and other external factors, and the quality of the seeds must be high, as it is good. The difference between the varieties of spring and autumn wheat in terms of the duration of the growing season is great. The duration of the growing season for spring wheat varieties is 70-80 days, for some varieties - 120-130 days, for autumn wheat varieties it can be 180-220 days or more, taking into account the winter dormancy period. This indicator also depends on the biological characteristics of the variety and the influence of external environmental factors.